Contour identical implants to bridge mandibular continuity defects - individually generated by LaserCUSING® - A feasibility study in animal cadavers. Issue 1 (December 2016) - Reitemeier, Bernd; Schöne, Christine; Lesche, Raoul; Lauer, Günter; Schulz, Matthias; Markwardt, Jutta
Abstract Background Ablative tumor surgery often results in continuity defects of the mandible. When an immediate reconstruction using autologous bone grafts is not possible the bridging of the defects with a variety of bridging plates might be achieved. However, those bridging plates have the risk of plate fractures or exposure. Customized titanium implants manufactured using CAD/CAM and the LaserCUSING® technique might be an alternative. Methods In the present study, computed tomographies (CT) of porcine cadaver mandibles were generated and transferred into DICOM data. Following, different continuity defects were surgically created in the mandibles. Based on the DICOM data customized titanium implants were manufactured using CAD/CAM procedures and the LaserCUSING® technique. The implants were fixed to the remaining stumps with screws. Subsequently, the accuracy of the reconstructed mandibles was tested using plaster casts. Results The workflow from the CT to the application of the customized implants was proved to be practicable. Furthermore, a stable fixation of the customized implant to the remaining stumps could be achieved. The control of the accuracy showed no frictions or obstacles. Conclusion The customized titanium implant seems to be a promising approach to bridge continuity defects of the mandible whenever an immediate reconstruction with autologous bone is not possible.